A Non-linear Association Between Total Small Vessel Disease Score and Hemorrhagic Transformation After Ischemic Stroke With Atrial Fibrillation and/or Rheumatic Heart Disease - Wei, Chenchen; Liu, Junfeng; Li, Jie; Liu, Ming (Frontiers in Neurology, 2019)
Background: Previous studies have investigated the association between a single marker of cerebral small vessel disease (SVD) and hemorrhagic transformation (HT). However, the effect of the total SVD burden on HT has not been evaluated yet. We aimed to investigate the association between the total SVD score and HT in ischemic stroke patients with atrial fibrillation (AF) and/or rheumatic heart disease (RHD). Methods: Ischemic stroke patients with AF and/or RHD admitted within 7 days after onset were enrolled at two hospitals in China. The total SVD score was based on the presence of lacunes, extensive white matter hyperintensities, cerebral microbleeds, and moderate-to-severe enlarged perivascular spaces in the basal ganglia. One point was awarded for the presence of each marker, with the total SVD score ranging from 0 to 4 points. HT was assessed based on follow-up imaging scans during hospitalization and was classified according to the radiographic appearance and associated neurological deterioration. Results: Of 207 enrolled patients (mean age 67.79 years, 58.9% female), 89 (43.0%) developed HT. The distribution of the total SVD score was significantly different between patients with and without HT in the univariate analysis (p=0.04). After adjustment for confounders, a SVD score of 1 was independently associated with an increased risk of HT [odds ratio (OR) 3.23, 95% confidence interval (CI) 1.48-7.04, p=0.003], while a SVD score ≥2 was inversely related to the occurrence of HT (OR 0.41, 95% CI 0.19-0.91, p=0.03). These independent associations remained significant in the subgroups of hemorrhagic infarction and asymptomatic HT (all p<0.05). Conclusions: In our study, the relationship between the total SVD score and HT was not linear, since the presence of only one marker of SVD was associated with an increased risk of HT, while the presence of two or more markers of SVD was a potential protective factor for HT. These results indicate the need to take the total SVD score into account, not only a single SVD marker, when assessing the risk of HT. Further studies with larger samples are required to validate these findings.